The Dynamics Of Negotiation And Accommodation Of Civil Society On Pesantren Education Policy - Fadhly Azhar; Asep Saepudin Jahar; Armai Arief; Muhammad Zuhdi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
In Indonesia, conflicts of interest regarding matters of religious education in Indonesia were not unique because the state and community interest groups tend to participate with each other in matters of education. The nation's ideological values and religious principles were interrelated, even experiencing interconnectivity. This conflict only occured in certain sub-sub-communities which had not yet fully reached state policy regarding religious education, where this encourages the politicization of education created by sub-dominant powers if an educational policy was not in accordance with the wishes and interests of the sub-dominant powers. This research aimed to identify and analyze the dynamics of negotiation and accommodation of civil society on Pesantren education policy. This research used a qualitative research approach with a case study method. The results of this research concluded that the involvement of Pesantren Kyai played a role in political interests in history before playing a role in legislative politics as happened in the Pesantren policy. The background to the involvement of Kyai in the Pesantren policy was born from the phenomenon that Kyai enjoyed a high social position since Islam entered Java in carrying out negotiation and accommodation efforts. There were two roles played by Kyai in the legal political constellation of the Pesantren policy. First, the formal role, where in this case the Kyai was a politician who has entered the political system. In this way, Kyai in this case also participates in carrying out party plans and activities, for example serving in the people's representative council, campaigns, work meetings and the like. Second, non-formal roles, in this case the Kyai had more status but then they also tried to approach politics itself. Kyai of this kind, structurally could not be said to be politicians, but socially they had a role in developing political circles.